(untitled) (Research, Society and Development, 2020)
The present study aims to determine the physical and chemical characteristics of the fresh extract and flour of the purple sweet potato over 30 days. The samples were divided into EI (Extract in natura), F0 (Flour day zero) and F30 (Flour day 30). To prepare the EI, the potatoes went through hygiene protocols and were subjected to grinding in the multiprocessor, whereas samples F0 and F30 followed the same hygiene process and were subjected to the drying process at 60ºC for 24 hours. Were analyzed for the physical-chemical parameters: Moisture content, ash, lipids, Total Soluble Solids (ºBrix), pH and acidity. As far as the physical-chemical analyzes were obtained, EI water content (70.4%) was higher in relation to samples F0 (9.72%) and F30 (10.76%). Ashes EI (0.036%), F0 (0.099%) and F30 (0.157%). Lipids EI 0.95, F0 0.31 and F30 0.29, characterizing them with low lipid content. The SST (ºBrix) EI 3.46ºBrix, F0 9.1ºBrix and F30 5.16ºBrix. The pH values are EI 6.62, F0 6.5 and F30 6.2. Acidity EI 0.30%, F0 1.01% and F30 0.95%. The analyzes carried out obtained satisfactory results successfully in the development and analysis of the product. According to the results, it is possible to observe that samples F0 and F30 are an alternative to be used in food products such as cakes, breads, cookies, and others, in order to improve nutritional quality and test new food technologies.